EFFECTIVENESS OF SADDLE BLOCK VS SPINAL ANAESTHESIA IN TURP: AN OPEN LABEL RANDOMIZED CONTROL TRIAL - Nida Shahid; Muhammad Wajid Iqbal; Syed Nurul Haque; Asim Masroor Rashid; Salman Shaukat (Journal of Ayub Medical College Abbottabad, 2023)
Background: One of the most frequent diseases among male gender is benign prostatic hyperplasia. Transurethral resection of the prostate (TURP) is a minimally invasive procedure for resection of prostate through endoscopic technique. Recently there was a debate on role of saddle block in TURP. There we aimed to determine the effectiveness of spinal anaesthesia versus saddle block in terms of hemodynamic stability and vasoprbessor requirement in TURP. Methods: This open label randomized control trial was performed at Hamdard University Hospital, Karachi, Pakistan, during 1st October, 2021 to 31st March, 2022. Male patients of age 45-65 years requiring TURP, with well controlled diabetes and hypertension of ASA grade I-II were included into the study and randomly assigned into two study groups. Patients’ parameters including blood pressure, heart rate, mean arterial pressure and oxygen saturation (SPO2) were measured at baseline and intraoperative at every fifth minute interval till surgery completion. Patients’ other parameters including age, surgery duration and comorbidity were also recorded. Results: Total 60 patients with 30 patients in each group were enrolled into the study. Maximum fall in systolic blood pressure, diastolic blood pressure, pulse rate and mean arterial pressure from baseline was significantly lower in patients receiving saddle block anaesthesia than spinal anaesthesia. Maximum fall in SPO2 was not significantly different among two study groups. Maximum fall in all parameters excluding SPO2 was significant between two groups for initial 20 minutes of the procedure. No statistically significant maximum fall was seen for all of the parameters beyond 20 minutes of the procedure. Vasopressor consumption was significantly lower in saddle block group than spinal anaesthesia. Conclusion: Application of saddle block anaesthesia is effective for TURP procedure with controlled hemodynamic status than spinal anaesthesia. Moreover, saddle block requires less vasopressor consumption than spinal anaesthesia technique.